Extracorporeal Membrane Oxygenation Supported Transbronchial Cryobiopsy in the Diagnosis of Severe Organizing Pneumonia: A Case Report - Zhang, Xiaoyan; Wang, Yuqiong; Feng, Yingying; Zhao, Ling; Zhang, Yunxia; Yang, Hanbo; Xing, Bin; Guo, Wenlin; Sun, Ting; Zhan, Qingyuan; Tian, Ye (Frontiers in Medicine, 2022)
This case report describes a 58-year-old, never-smoking housewife with chief complaints of progressively worsening cough, dyspnea, and intermittent fever, who was initially misdiagnosed with community-acquired pneumonia (CAP). Fortunately, transbronchial cryobiopsy (TBCB) assisted by extracorporeal membrane oxygenation (ECMO) was performed in the most critical situation, and it revealed an organizing pneumonia (OP) pattern. OP describes a histological pattern of acute or subacute pulmonary damage, which may be idiopathic or associated with a known or unknown underlying disease, leading to delay in diagnosis, or even misdiagnosis. A definitive diagnosis is usually obtained from lung biopsy because of the unavailability of other specific detection methodologies. To our knowledge, we are the first to report the pathological diagnosis of ECMO assisted TBCB in acute respiratory failure. When oxygenation cannot be maintained after endotracheal intubation and surgical lung biopsy is not feasible, ECMO-supported TBCB may be a good choice to obtain lung tissue for histopathological diagnosis in patients with acute lung injury of unknown etiology.